Purple coloration in leaves of seagrass, Halophila (Hydrocharitaceae) - Bujang, Japar Sidik; Zakaria @ Ya, Muta Harah (Academic Journals, 2013)
Purple coloration in leaves of Halophila from Merambong shoal of Sungai Pulai estuary, Johore and Merchang, Terengganu, Malaysia were investigated using a simple detection method based on chemical properties of anthocyanin that changes from red in acids to blue in bases. In addition the presence of anthocyanin was examined for the absorption maxima at wavelengths between 505 to 535 nm and phycoerythrin absorption maxima at wavelengths 496, 540 and 656 nm. Based on responses of color change in acid and base, Halophila from Merambong shoal (green big-leaved Halophila ovalis, green small-leaved Halophila ovalis, green-leaved Halophila sp.) lacked anthocyanins. Purple-tinged-leaved Halophila sp. from Merambong, purple-blotched-leaved Halophila sp. from Merchang and purple-tinged-leaved Halophila sp. (explant from Merambong shoal) from culture tank showed dramatic changes from purple-tinged or-blotched to blue-green tinged or -blotched respectively in 2 M NaOH or reddish coloration appeared exactly on blotches and tinges of leaves after dipping in 2 M HCL. The results for the latter three seagrasses agreed with the response of anthocyanins in base (NaOH) or acid (HCL) and the presence of anthocyanin was further confirmed with the results of absorption spectra maxima obtained at 535 nm. The detection of phycoerythrin with absorption maxima at 496, 540 and 656 nm in the purple leaves Halophila indicated that they lack this pigment. Seaweed e.g., Jania sp. showed positive detection for phycoerythrin with absorption maxima at 495 and 565 nm.